Mesenchymal hamartoma of the chest wall: Prenatal sonographic manifestations. Issue 6 (30th May 2013) - Wie, Jeong ha; Kim, Ju Yeon; Kwon, Ji Young; Ko, Hyun Sun; Shin, Jong Chul; Park, In Yang
Abstract Mesenchymal hamartoma of the chest wall is a rare, benign lesion that arises from one or more ribs, almost exclusively found in infants. Some cases that developed in the fetal period have been reported, but accurate diagnosis was usually possible only after birth, except in a few cases in which fetal magnetic resonance imaging or computed tomography were performed. We present a case of a congenital mesenchymal hamartoma of the chest wall. Although the diagnosis was not confirmed until birth, the prenatal sonographic examination showed strongly suggestive findings. We review the published reports on this condition, and suggest the prenatal sonographic features. Prenatal sonography is valuable in the differential diagnosis of chest mass.